To gel or not to gel: correlating molecular gelation with solvent parameters1. (7th October 2015) - Lan, Y.; Corradini, M. G.; Weiss, R. G.; Raghavan, S. R.; Rogers, M. A.
<x xml:space="preserve">Abstract</x> Solvent parameters provide an understanding into the driving forces governing SAFiN formation aiding in the quest for a universal gelator.